A Morphometric Study of Sacrum With Five Pairs of Sacral Foramina (GAIMS Journal of Medical Sciences, 2023)
Background:The sacrum is formed by five sacral vertebra fused into a triangle and forming the posterior upper wall of the bony pelvis. Numerous anatomical variations of the sacrum have been reported, with complete bilateral sacralization of the 5th lumbar vertebra or complete bilateral sacralization of the 1st coccygeal vertebra of various breeds producing a sacrum with five pairs of sacral foraminae. Aims and Objectives:This study was designed to determine the prevalence of sacrum with five pairs of sacral foramina.Materials and methods:The study was conducted in the Department of Anatomy at K.J.Somaiya Medical College, Mumbai.100 dried human sacrum were examined out of which 12 specimens having five pairs of sacral foramen representing bilateral full sacralization of the fifth lumbar vertebra were observed  and 7 specimens having bilateral full sacralization of the first coccygeal vertebra were found.Results:The prevalence of 5-paired sacral foramen sacrum varies in the general population and has not been reported separately. The present study shows that the incidence of  sacrum with five pairs of sacral holes is 12%. The prevalence of sacrum with five pairs of sacral foramina sacralization of the  the 1st coccyx is 7%, respectively.Conclusion:Knowledge of this anatomical variation is of paramount importance to spine surgeons, obstetricians, radiologists, coroners, morphologists, and clinical anatomists.